The only ones - Starmer, Aaron (New York : Delacorte Press, 2011)
After setting off from the island where he has been leading a solitary existence, thirteen-year-old Martin discovers a village, Xibalba, peopled with other children who have been living and governing themselves since the grown-ups were all spirited away.
700L
Keywords: Leadership; Ability; Conduct of life; Science fiction; Paranormal fiction